Nutritional characteristic of children with inflammatory bowel disease in the nationwide inflammatory bowel disease registry from the Mediterranean region - Kuloglu, Zarife; Çetin, Funda; Urgancı, Nafiye; Önal, Zerrin; Sarı, Sinan; Yüksekkaya, Hasan; Yücel, Aylin (Springer Nature, 2022)
Background/objectives: We analyzed the nationwide pediatric inflammatory bowel disease (PIBD) registry (1998–2016), to evaluate the nutritional status at the time of diagnosis. Subjects/methods: Nine types of nutritional status by the combination of weight-for-length (<2 years)/body mass index (>2 years) and length/height-for-age with three categories (<?2, ?2 to 2, and >2 SD) were described. Malnutrition was defined by WHO criteria. Univariate and multivariate regression analysis was used to identify risk factors for malnutrition. Results: In total, 824 IBD patients (498 Ulcerative colitis (UC); 289 Crohn’s Disease (CD); 37 Indeterminate Colitis (IC); 412 male; the median age 12.5 years) were eligible. The prevalence of eutrophy, wasting/thinness, stunting, overweight, tall stature, concurrent wasting/thinness and stunting, tall stature with overweight, tall stature with wasting/thinness, and short stature with overweight were 67.4%, 14.9%, 6.6%, 3.1%, 3.2%, 3.3%, 1.1%, 0.4%, and 0.1%, respectively. The prevalence of malnutrition was 32.7%, indicating a higher prevalence in CD (p < 0.001). Incidence of overweight was less common in the CD than UC and IC (p < 0.001). Multivariate analysis revealed that age of onset (>10 years), prepubertal stage, severe disease activity, perianal involvement, and high C reactive protein level were independently associated with malnutrition in pediatric IBD. Conclusion: We showed the frequency of nutritional impairment in PIBD. The percentage of overweight subjects was lower than the other studies. The age of onset, disease activity, CRP level, perianal involvement, and pubertal stage were associated with a higher risk for developing malnutrition. Our results also confirmed that CD patients are particularly vulnerable to nutritional impairment. Clinical trial number: ClinicalTrials.gov Identifier: NCT04457518. © 2022, The Author(s), under exclusive licence to Springer Nature Limited.
Keywords: C reactive protein; anemia; anthropometric parameters; Article; body mass; breast feeding; child; Crohn disease; cross-sectional study; disease activity; erythrocyte sedimentation rate; female; human; hypoalbuminemia; inflammatory bowel disease; leukocytosis; male; malnutrition; multicenter study; nutritional assessment; nutritional status; obesity; observational study; onset age; pancolitis; patient selection; risk factor; short stature; socioeconomics; Southern Europe; stunting; tall stature; thrombocytosis; ulcerative colitis